Three-dimensional reconstruction and characterization of human external shapes from two-dimensional images using volumetric methods - Teresa C. S. Azevedo (2010)
This work presents a volumetric approach to reconstruct and characterize three-dimensional (3D) models of external anatomical structures from two-dimensional (2D) images. Volumetric methods represent the final volume using a finite set of 3D geometric primitives, usually designed as voxels. Thus, from an image sequence acquired around the object to reconstruct, the images are calibrated and the 3D models of the referred object are built using different approaches of volumetric methods. The final goal is to analyze the accuracy of the obtained models when modifying some of the parameters of the considered volumetric methods, such as the type of voxels projection (rectangular or accurate), the way the consistency of the voxels is tested (only silhouettes or silhouettes and photo-consistency) and the initial size of the reconstructed volume.